(untitled) (Journal of Dhaka Medical College, 2015)
Fifty four cases of histopathologically or cytopathologically confirmed tuberculosis of the breast were found during a period of 3 years in surgery outpatient department of Dhaka Medical College Hospital, Dhaka, which was accountable for 2.42% of all breast diseases. All the patients were female. Most of the cases were in third and fourth decades. Among them, 3 patients were lactating and 1was pregnant. Diagnosis was suspected clinically on the basis of lump or lumpiness and/or solitary or multiple chronic discharging sinuses in the breast or axilla. Breast lumps in 33 cases simulated carcinoma. Histopathological examination was done to establish the nature of the pathology. All patients were treated with four drug combination (4FDC) anti tubercular therapy for 12 months. However, forty patients required some forms of surgery DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21539 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 185-187